MADRID, Nuria S. A civilização como destino: Kant e as formas da reflexão. Florianópolis: Nefiponline, 2016. ISBN 978-85-99608-16-6 - Calovi, Gustavo Ellwanger (Studia Kantiana, 2017)
MADRID, Nuria S. A civilização como destino: Kant e as formas da reflexão. Florianópolis: Nefiponline, 2016. ISBN 978-85-99608-16-6